Mechanism of stress induced crystallization of polyethylene. (26th June 2019) - Yakovlev, Sergey; Fiscus, David; Brant, Pat; Butler, Jeff; Bucknall, David G.; Downing, Kenneth H.
Abstract: When polymer melt is subjected to stress, molecular chains become aligned along the elongation direction. However, when polyethylene film crystallizes under stress, molecular chains frequently align perpendicular to the elongation direction. In this paper we investigate why this happens. Evaluating metallocene LLDPE film we show that under the stress lamellae rotate to accommodate geometrical changes. Quantitative analysis of SAXS data explains the mechanism of this rotation. The lamellae rotation presents an opportunity to reexamine the strain-induced structure and crystallization mechanism. For the first time we apply 3D visualization to shish-kebab like structure in bulk samples and support visualization with Fourier analysis to relate the microscopy data to large body of evidence reported earlier by SAXS. Obtained evidence reveals that our samples do not contain extended chain precursors. Reevaluation of the equatorial streak, frequently interpreted as evidence of extended chain precursors or voids, suggests that in our sample the streak originates from rotated lamellae. Our findings indicate that strain-induced crystallization does not have to rely on the existence of extended chains precursors, as is widely assumed. While the major findings from this work are derived from microscopy investigations we supplement these with limited amount of SAXS and WAXS experiments to help elucidate the rotation mechanism and crystalline orientation. The insight dervied from this study reconciles seemingly contradictory SAXS, WAXS, TEM and optical microscopy data collected from polyethylene film. Graphical abstract: Image 1 Highlights: Deformation of oriented semi crystalline polyethylene causes rotation of lamellae stacks. Equatorial streak in SAXS pattern originates on reminds of lamellae stack rather than on extended chain precursors or voids. Deformation, causing stress induced crystallization, can rotate newly crystalized lamellae and reorient molecular chains.